Advantage Of Treatment of Industrial Wastewater Using the Coagulation Method - Karimova F.S; Jurayeva .U.B (Genius Publishing Group, 2024)
This article describes the coagulation method, its working principles and advantages from the physico-chemical treatment methods of wastewater.
Keywords: Wastewater; reagent; coagulation